Large curvature analysis of two-dimensional linear elastic frames by direct stiffness method /|cJongaphonh Douanevanh - Jongaphonh Douanevanh (Chulalongkorn University, 2013)
Thesis (M.Eng.)--Chulalongkorn University, 2011